Green Education as an Approach to Enhancing Psychological and Social Adaptation among Libyan University Students: Toward an Integrative Model for Achieving Sustainable Development (Al-Farooq Journal of Sciences, 2026)
In light of accelerating environmental and social transformations, green education has emerged as a strategic approach to achieving sustainable development—not only from an environmental perspective but also as a psychosocial framework that fosters balanced and adaptive individuals. Accordingly, this study aims to develop a conceptual and empirical model examining the role of green education in enhancing psychological and social adjustment while reducing psychological alienation among Libyan university students.The research problem arises from the limited integration of green education dimensions within Libyan higher education institutions, alongside increasing indicators of psychological alienation among students, reflecting a gap between educational outputs and sustainable development requirements.A descriptive-analytical method was employed, with a random sample of (150) students from the University of Benghazi to ensure broader representativeness. Two primary instruments were utilized: the Psychological Alienation Scale and the Green Education Attitude Scale (developed by the researchers). Validity and reliability were confirmed, with Cronbach’s alpha reaching (α = 0.87).Data were analyzed using SPSS, applying descriptive statistics, Pearson correlation, independent samples t-test, and one-way ANOVA. The findings revealed a strong, statistically significant negative correlation (r = -0.62, p ≤ 0.01) between the adoption of green education and psychological alienation, indicating that sustainable educational practices significantly contribute to improving students’ psychological well-being. Additionally, significant gender differences were found in favor of females regarding green education awareness (t = 2.41, p ≤ 0.05), while no significant differences were observed based on academic specialization (F = 1.12, p > 0.05).The study contributes theoretically and practically by proposing an integrative model linking green education with psychosocial adjustment dimensions, offering valuable implications for policymakers and educators in developing sustainable higher education strategies in Libya. It further recommends embedding green education into curricula, fostering institutional partnerships, and promoting educational innovation aligned with sustainable development goals.